Heterogeneous activation of persulfate by Co3O4-CeO2 catalyst for diclofenac removal. (15th March 2019) - Xian, Guang; Zhang, Guangming; Chang, Huazhen; Zhang, Yi; Zou, Zhiguo; Li, Xueyan
Abstract: A series of Co3 O4 -CeO2 mixed metal oxides were synthesized by co-precipitation method and successfully used to activate persulfate for diclofenac removal. The effects of Co:Ce mole ratio, calcination temperature and calcination time on the catalytic activities were investigated. Results showed that the activity of Co3 O4 -CeO2 catalysts increased with Co:Ce mole ratio from 1:9 to 7:3, and decreased with the calcination temperature from 300 to 800 °C. 90% diclofenac was removed with Co7 Ce3 -300-1 catalyst (Co:Ce = 7:3, calcinated at 300 °C for 1 h) after 15 min. Moreover, short calcination time and low temperature resulted in smaller crystallite size, more structural defects, more active crystal surfaces and larger surface area of the catalyst, which led to higher removal efficiency of diclofenac. The high ratios of Co 2+ /Co 3+, Ce 3+ /Ce 4+ and Oads /Olatt were very important to enhance the catalytic activity. Finally, a potential reaction mechanism was proposed based on characterization of the fresh and spent catalysts. Graphical abstract: Image 10240661 Highlights: Co3 O4 -CeO2 was synthesized to activate persulfate for diclofenac removal. The activity was affected markedly by Co:Ce mole ratio and calcination temperature. Interaction among Co, Ce and O species was the basis of high catalytic activity. Redox between Co and Ce was vital for sustaining the activity of the catalyst.